Social-psychological influences and the process of personality socialization in candition of transformations - Garkavets, S. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article analyzes the possibility of types and methods of the social and psychological impact, and find out which ones are the most effective on the implementation of the requirements of the youth society in terms of transformational change. The results of empirical study, which found that the higher is the level of needs, the more rational the individual, and in real life he mainly use their best judgment with respect to the fulfillment of social needs.
Keywords: impact; personality; socialization; transformational change